2003
DOI: 10.1162/089892903321593162
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of the Left-Visual-Field Superiority in Face Perception Appear at Multiple Stages of Face Processing

Abstract: Studies in healthy individuals and split-brain patients have shown that the representation of facial information from the left visual field (LVF) is better than the representation of facial information from the right visual field (RVF). To investigate the neurophysiological basis of this LVF superiority in face perception, we recorded event-related potentials (ERPs) to centrally presented face stimuli in which relevant facial information is present bilaterally (B faces) or only in the left (L faces) or the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
44
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 32 publications
14
44
1
2
Order By: Relevance
“…Shorter latencies of face-specific N170 in the right hemisphere were reported by other authors (Yovel et al, 2003). The early match-mismatch effects in the Face task observed in the scalp-recorded ERPs in 200 -250 ms (Mnatsakanian and Tarkka, 2003) can be explained by differences in the activity of the sources 2, 4, 5, and 8 in our models.…”
Section: Discussionsupporting
confidence: 69%
“…Shorter latencies of face-specific N170 in the right hemisphere were reported by other authors (Yovel et al, 2003). The early match-mismatch effects in the Face task observed in the scalp-recorded ERPs in 200 -250 ms (Mnatsakanian and Tarkka, 2003) can be explained by differences in the activity of the sources 2, 4, 5, and 8 in our models.…”
Section: Discussionsupporting
confidence: 69%
“…In physiological studies using fMRI, right FFA was activated more than left FFA [23,24]. Using ERP and MEG, most subjects evoked larger components for face in the right hemisphere than the left [10,11,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 92%
“…Second, most, if not all, acquired prosopagnosics follow either bilateral or right unilateral occipitotemporal lesions (Bouvier and Engel, 2006;Landis et al, 1988). Third, neuroimaging (Kanwisher et al, 1997;McCarthy et al, 1997;Rossion et al, 2012) and ERP (Bentin et al, 1996;Rossion et al, 2003;Yovel et al, 2003) studies have also demonstrated the right hemispheric dominance for face recognition.…”
Section: Interhemispheric Variabilitymentioning
confidence: 99%